Proteinograma sérico de cães sadios e com linfoma obtido por eletroforese em gel de poliacrilamida (SDS-PAGE) - Calazans, S. G. [UNESP]; Daleck, C. R. [UNESP]; Fagliari, J. J. [UNESP]; Repetti, C. F.; De Nardi, A. B.; Castro, J. H.T. [UNESP]; Fernandes, S. C. [UNESP]; César, J. R.F. [UNESP]; Rodigheri, S. M. [UNESP] (FapUNIFESP (SciELO), 2009)
Blood serum samples of ten healthy dogs and 12 dogs with lymphoma were evaluated by means of sodium dodecil sulphate-polyacrylamide gel electrophoresis. There was difference in total protein concentrations among healthy dogs, 7.68g/dL±0.46 and dogs with lymphoma, 7.93g/dL±2.49 values of immunoglobulins A and G presented no difference between groups. Serum proteins with molecular weights 142,000; 110,000; 52,000; 49,000; 24,000; and 18,000 Daltons presented increased concentrations in dogs with lymphoma. Dogs with lymphoma presented increased ceruloplasmin (43.95mg/dL±18.19) and haptoglobin (554mg/dL±449.51) values and lesser albumin concentration (2,908mg/dL±476.67) when compared to healthy dogs (ceruloplasmin: 3.42mg/dL±7.44; haptoglobin: 94.54mg/dL±59.50, and albumin: 4,207mg/dL±206.18). In conclusion, increased ceruloplasmin and haptoglobin and lesser albumin serum concentrations are possibly related to lymphoma in dogs.
Serum protein concentrations in healthy dogs and dogs with lymphoma by means of sodium dodecil sulphate-polyacrylamide gel electrophoresis (SDS-PAGE)
Keywords: Dog; Lymphoma; Serum protein